2019
DOI: 10.3390/ma12071021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Singular Value Truncation Method for Non-Destructive Evaluation of Structural Damage Using Natural Frequencies

Abstract: As natural frequencies can be easily and accurately measured, structural damage evaluation by frequency changes is very common in engineering practice. However, this type of method is often limited by data, such as when the available natural frequencies are very few or contaminated. Although much progress has been made in frequency-based methods, there is still much room for improvement in calculation accuracy and efficiency. To this end, an enhanced singular value truncation method is proposed in this paper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…An enhanced singular value truncation method is proposed in paper [22] to evaluate structural damage more effectively by using a few lower order natural frequencies. The main innovations of the enhanced singular value truncation method lie in two aspects.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced singular value truncation method is proposed in paper [22] to evaluate structural damage more effectively by using a few lower order natural frequencies. The main innovations of the enhanced singular value truncation method lie in two aspects.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…In the numerical examples, it was found that the proposed method can successively obtain more accurate damage evaluation results compared with the traditional singular value truncation method. In the experimental example, it was shown that the proposed method possesses more precise and fewer calculations compared with the existing optimization algorithms [22].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The natural frequency of a mechanical system is a core parameter of reflecting dynamic characteristics, which plays an important role in many dynamic research fields such as vibration control, fault diagnosis, and structural optimization design [1][2][3][4][5][6]. Determining or calculating natural frequency is one of the main tasks of structural dynamic analysis, which has great theoretical value and practical engineering applications background [7].…”
Section: Introductionmentioning
confidence: 99%
“…In structural vibration modal analysis, the eigenvalue (square of frequency) and eigenvector (mode shape) are the two important parameters and their sensitivities are often used in many engineering problems such as structural vibration control [1][2][3][4][5][6], optimization design [7][8][9], model updating [10][11][12][13][14] and damage identification [15][16][17]. From the current research literature, the calculation formula of eigenvalue sensitivity is simple, but the calculating formula for eigenvector sensitivity is complicated.…”
Section: Introductionmentioning
confidence: 99%